The Curious Case of a Robot Doctor: "Human," Labor and Expert Systems. - Xiao LIU (Frontiers of Literary Studies in China, 2016)
While Amazon Mechanical Turk project refreshes the long-term dream of artificial intelligence by incorporating human beings into the automation of information circuits, it also calls attention to the role of technical platforms in reorganizing the division and mode of labor under the current information capitalism. This essay examines this transformed labor regime by outlining the discourses and imaginaries of Artificial Intelligence (AI) in late 1970s and 1980s China when expert systems--an artificial intelligence system designed to provide expert consultation in the absence of human experts--first appeared. I argue that these discourses and imaginaries surrounding expert systems were tied to the anticipation of a coming information society, and to the fetish of expert knowledge, and a shift from Mao's class-based politics to a depoliticized realm of professionalism. Bringing together the material, technical development of AI, the intellectual discourse of Post-Mao 1980s, as well as the imaginary domain of science fiction, this essay rethinks the politics of the "human" in the social context of Post-Mao's era.